Katy Perry the movie : part of me - Cutforth, Dan, 1967-; Lipsitz, Jane, 1965- (Burbank, CA : Warner Home Video, 2013)
Follows Katy Perry as she prepares for her California dreams world concert tour and shares footage of her life growing up and on-and-off the stage.
Concert footage filmed live at the Staples Center, Los Angeles, Calif., Nov. 23, 2011.
Not rated.
Blu-ray disc, DTS-HD Master Audio 5.1.
This is a Blu-ray disc which can only be played on Blu-ray disc players and will not play on standard DVD players.
Keywords: Perry, Katy; Women singers -- United States -- Biography; Documentary films; Nonfiction films; Feature films; Biographical films